ANALISIS IMPLEMENTASI PENCEGAHAN PENCUCIAN UANG MENGGUNAKAN CUSTOMER DAN ENHACED DUE DILLIGENCE DI BANK SYARIAH MANDIRI JAKARTA - Siti Noviatun; Isfandayani - (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2020)
Abstract The main fuction of the Bank as an funding and lending activities by offering various types of financial transaction services an attractive choice for people who do money laundering to hide money proceeds of crime. Because of that the government and Indonesian Banks make regulations related prevent money laundering that contains Customer Due Dilligence and Enhanced Due Dilligence. Bank Mandiri Syariah has implementation Customer Due Dilligence and Enhanced Due Dilligence as an effort to prevent money laundering. This analyze aims for knowing implementation Customer Due Dilligence and Enhanced Due Dilligence that has been applied by Bank Syariah Mandiri. In this study using a qualitative descriptive method. Data retrieval is done by observation, interviews and documentation to three sources of informants Bank Syariah Mandiri KCP Bekasi Timur and one sources of informants that specifically handles money laundering prevention program that is SKAP( Satuan Kerja APU PPT) Bank Mandiri Syariah. Data analysis will be done by doing three steps, they are; data reductions, data display, and verification.The observation result shows that implementation Customer Due Dilligence done at the time prospective customer open the account and the Bank doubt information customer by doing identification and verification. implementation Enhanced Due Dilligence is done to customers Politically Exposed Person/ High Risk open the account, but in practiceat Bank Syariah Mandiri KCP Bekasi Timur done when there is suspicious transaction or there is a case. Reporting process suspicious transaction through the system SIAP (System Aplikasi APU PPT) to Satuan Kerja APU PPT (SKAP) Bank Syariah Mandiri then SKAP reports to PPATK (Pusat Pelaporan Analisis Transaksi Keuangan). From implementation Customer Due Dilligence and Enhanced Due Dilligence Bank Mandiri Syariah has been prevent money laundering enter the financial system at Mandiri Sharia Bank.